Spanish refugees in Portugal and the Portuguese solidarity (1936-1945) - Fábio A. Faria (Culture & History Digital Journal)
This article aims to analyze the reception and route of refugees through Portugal in the context of the Spanish Civil War, a territory that, due to its geographical proximity, was especially sought as a place of refuge by countless Spaniards to protect themselves from war and persecutions. Due to its authoritarian nature, Salazar´s regime proved reluctant to receive them and developed a repression directed at these refugees, considered “undesirable,” visible in the increase of the number of border posts and their reinforcement and in the collaboration between different authorities, namely PVDE (State Surveillance and Defense Police), GNR (Republican National Guard), PSP (Public Security Police) and GF (Fiscal Guard), leading to their concentration in large national prisons. In the context of the phenomenon of the Spanish Republican refugees in Portugal, this article also discusses the role played by the Portuguese population and by some elements of the authorities in the assistance provided to Spanish refugees, as well as the repression that was driven by Salazar’s regime.